Design elements evoke embodiment at cultural sites in Rwanda and South Africa. (June 2023) - Stanford, Ruth
Design elements, the physical or architectural choices that determine the character of space, can have a dramatic effect on visitor experience at museums and memorial sites. At those employing strategies of embodiment, viewer experience takes on added significance. Many contemporary memorial sites employ physical touchstones that evoke emotional experiences, giving viewers a deeper empathy for injustice or humanitarian tragedy. This visual essay examines design elements—such as architectural details and the placement of objects—that evoke embodiment at three sites: the Bisesero genocide memorial in Rwanda and the Apartheid Museum and Prestwich Memorial museum in South Africa. Each of these sites manifests design elements that encourage visitors to engage physically and emotionally with the victims of historical atrocities. Moving visitors beyond a detached, intellectual understanding of traumatic histories toward a physical/emotional engagement may engender a deeper connection with humanitarian tragedy and the struggle for healing and reconciliation.